Discovery of dual targeting PEGylated BG-P1600-TAT to norepinephrine transporter (NET) and thyrointegrin αvβ3 in the treatment of neuroblastoma. (1st August 2021) - Ozen Karakus, Ozlem; Godugu, Kavitha; Mousa, Shaker A.
Graphical abstract: Abstract: Polymer-drug conjugates are growing in interest as novel anticancer agents for targeted cancer therapy. The aim of this study was to synthesize a poly(ethylene glycol) (PEG) conjugated anticancer drug for neuroblastoma, which is the most common extracranial solid tumor of childhood and the deadliest tumor of infancy. In our previous studies, we designed and synthesized a dual targeting agent using benzylguanidine (BG) conjugated with the high affinity thyrointegrin αvβ3 antagonist TriAzole Tetraiodothyroacetic acid (TAT) via non-cleavable bonding to PEG400 to make BG-P400 -TAT and its derivatives as agents against neuroblastoma. Here, we improved the pharmacodynamic properties and increased the solubility by changing the polymer length to 1600 molecular weight. The TAT group, which acts as an integrin αvβ3 antagonist, and the BG group, which can be taken up by neuroblastoma cells through the norepinephrine transporter (NET) system, are conjugated to PEG1600 to make BG-PEG1600 -TAT. The binding affinity of BG-PEG1600 -TAT was 40-fold higher to integrin αvβ3 versus BG-P400 -TAT and was associated with greater anticancer activities against neuroblastoma cells (SK-N-F1 and SKNAS) implanted in SCID mice along with broad spectrum anti-angiogenesis activities versus the FDA approved anti-Vascular Endothelial Growth Factor (VEGF) monoclonal antibody Avastin (bevacizumab). In conclusion, our novel dual targeting of NET and αvβ3 receptor antagonist, BG-P1600-TAT demonstrated broad spectrum anti-angiogenesis and anti-cancer activities in suppressing neuroblastoma tumor progression and metastasis. Thus, BG-PEG1600 -TAT represents a potential clinical candidate for targeted therapy in neuroblastoma management.